PROSES PENDAMPINGAN DAN PENGEMBANGAN BAGI PARA UMKM DI KELURAHAN DARMO, KEC. WONOKROMO, SURABAYA - Kamala Nailil Muna; Ririt Iriani Sri S; Putra Perdana (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
At KKN-T (Real-Thematic Work Lectures) with our partners UMKM Darmo Village. Micro, Small and Medium Enterprises (MSMEs) are one of the important factors in supporting the wheels of the Indonesian economy that are able to encourage economic growth. There are MSME problems in Indonesia that have not been maximally resolved, especially MSMEs located in Darmo Village, Wonokromo District, Surabaya where most of the people are still technologically stuttering, this makes MSME actors not progressing so they do not reach digital marketing. In community service activities carried out by providing assistance and digital market- based business development in Darmo Village, Wonokromo District, Surabaya. We use several methods including interviews and observation. This method is used as a mapping by prioritizing problems first, collecting data and information, selecting the right solution for selected MSMEs, and implementing mentoring. high level of effort, following community trends, lastly creating added value for the products sold as well as developing aspects of digital-based product marketing. In this service, we can achieve the results of developing MSMEs in digital marketing. This service program was carried out in Darmo Village, Wonokromo District, Surabaya City.